The Impact of the Increase in Non-regular Employment on Income Disparities - Inagaki, Seiichi (Journal of Income Distribution®, 2007)
In Japanese society, changes in the employment patterns of the youth, particularly the increase in non-regular employment, have the potential to widen income disparities in the future. These potential income disparities are hidden because the youth who are not engaged in regular employment continue to live with their parents. This article attempts to reveal these latent income disparities by two methods: (1) observing the Gini coefficient that is based on virtual households by splitting the current households into adult/couple units and (2) measuring future income disparities by using a microsimulation model. The results of both methods reveal that latent income disparities do actually exist.